Acute effects of different electrical stimulation currents and phase durations on muscle: a randomized crossover trial (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: Neuromuscular electrical stimulation (NMES) is a relevant therapeutic strategy in the context of rehabilitation. Different NMES waveforms have been used to evoke contractions. Conventional NMES consists of pulsed currents (PC) with phase/pulse durations